2019
DOI: 10.1039/c9tc00326f
|View full text |Cite
|
Sign up to set email alerts
|

High-performance blue fluorescent/electroactive polyamide bearing p-phenylenediamine and asymmetrical SBF/TPA-based units for electrochromic and electrofluorochromic multifunctional applications

Abstract: A novel EC/EFC polyamide is realized by introducing stably electroactive p-phenylenediamine and asymmetrical SBF/TPA-based unit to reduce packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Su et al reported in this way a novel blue fluorescent/electroactive polyamides with the asymmetric spirobifluorene‐triphenylamine (SBF)/TPA groups (SBF‐HPA) (Scheme 2b). [ 36 ] The aliphatic cyclohexyl portion in the polyamide backbone serves again to enhance the fluorescence intensity by reducing the charge transfer between the TPA donor and the amide acceptor, as already observed in the previous TPA‐MeS polymers. The SBF substituent does effectively act as ACQ mitigation in that the fluorescence quantum yield of the polymer decreases from 70% in solution to 14% in the film.…”
Section: Electrofluorochromic Polymersmentioning
confidence: 80%
See 1 more Smart Citation
“…Su et al reported in this way a novel blue fluorescent/electroactive polyamides with the asymmetric spirobifluorene‐triphenylamine (SBF)/TPA groups (SBF‐HPA) (Scheme 2b). [ 36 ] The aliphatic cyclohexyl portion in the polyamide backbone serves again to enhance the fluorescence intensity by reducing the charge transfer between the TPA donor and the amide acceptor, as already observed in the previous TPA‐MeS polymers. The SBF substituent does effectively act as ACQ mitigation in that the fluorescence quantum yield of the polymer decreases from 70% in solution to 14% in the film.…”
Section: Electrofluorochromic Polymersmentioning
confidence: 80%
“…[25][26][27] However, we are going to show that, besides some excellent reviews [22,28,29] published early in the last decade, there was a significant number of scientific articles published in the last few years, demonstrating the increasing interest on electrofluorochromism, both from a technological evolution point of view and from the academic ones. All these publications are mainly focused on EFC materials development [30][31][32][33][34][35][36] (i.e., organic, inorganic, hybrid-based, small molecules or polymer-based), highlighting, on the other hand, the lack of a significant development of the related EFC devices and applications. Another critical issue in this field is the quantitative evaluation of the materials/devices performances.…”
mentioning
confidence: 99%
“…To further investigate the interesting "colorless-to-black" EC properties, spectroelectrochemical analyses, in which the optical properties of the thin polymer film could be studied in situ with a UV−vis spectrophotometer in response to the Z-12TPE-PA films showed large contrast ratios (Δ% T) for 86, 93, and 92%, respectively, which were much higher than most of the reported EC materials. 14,23 Additionally, the oxidation of the polymer films using chemical oxidants was also investigated, and the corresponding absorption changes are shown in Figure S17. Here, Cu(ClO 4 ) 2 was chosen as the chemical oxidant because of its not showing absorption or emission in the UV/Vis region at low concentrations.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Electrofluorochromism deals with the reversible modulations between different fluorescence states in response to an external redox stimulus. Because of the widespread impact, for example, for applications ranging from displays to sensors and memories, EFC materials have been intensively studied, including the species of redox-active molecules, multilayer/bulk-heterojunction composites, and electroactive/fluorescent polymers. Compared with other species, EFC polymers are advantageous for their fast response speed, competitive processability, and facile structural modifications. Although a few EFC polymers have been reported, designing suitable EFC polymers that offer high fluorescence contrast, rapid switching speed, long-term stability, as well as low-cost production remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…5–9 Liou prepared PAs with high contrast transmittance from colorless to black between bleached and colored states when oxidized. 13 Sun synthesized PAs with fast response; 14 Liaw prepared PIs with strong optical contrast. 15 PAs with pyrene, TAA derivatives and spirofluorene as the core synthesized by our group have good physicochemical stability and electrical properties.…”
Section: Introductionmentioning
confidence: 99%